A generalized Jaynes-Cummings Hamiltonian and supersymmetric shape invariance - Aleixo, ANF; Balantekin, A. B.; Ribeiro, MAC (Iop Publishing Ltd, 2000)
A class of shape-invariant bound-state problems which represent two-level systems are introduced. It is shown that the coupled-channel Hamiltonians obtained correspond to the generalization of the Jaynes-Cummings Hamiltonian.